Uniqueness theorems for rational, algebraic, and algebroid functions - Gol'dberg, A. A.; P'yana, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A number of points $A$, for which one must define the sets of simple $A$-points to determine a rational function, a polynomial, and an algebraic or algebroid function uniquely, is obtained.